Pemanfaatan Perpustakaan Keliling Dinas Perpustakaan dan Kearsipan Kota Padang Sebagai Penunjang Program Pendidikan Dalam Mengenalkan Literasi Informasi Pada Siswa SD - Mitria, Mitria; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractUse of the Mobile Library The City of Padang Library and Archive Office as a Supporting Education Program in Introducing Information Literacy to Elementary School Students. Based on the results of the study it can be concluded that general knowledge books are very helpful for elementary students in using for reading and as students increase their knowledge in improving information literacy, story books are able to increase students 'interest and can also increase students' insight into personal and social problems, and fiction books used by students as a means of entertainment reading outside the learning activities in the classroom, Secondly, the constraints in the use of mobile library based on the results of the research obtained were limited time, lack of human resources (HR), and lack of facilities and infrastructure, Third, efforts to overcome utilization constraints mobile libraries based on the results of research that the authors obtain can be concluded is by increasing service time in schools, adding service employees, and adding cars for service to schools.Keywords: utilization, mobile library, education, literacy, and elementary students.